A Multi-Criteria Sustainability Assessment of Mediterranean Rainfed Farming Systems using the IDEA Method: A Moroccan Case Study - Fatiha Hakimi; Fatima Zahra Hamdoun (Caraka Tani: Journal of Sustainable Agriculture, 2023)
Sustainable agriculture in arid and semi-arid regions faces unique challenges that require targeted assessment and intervention. Addressing the knowledge gap in this context, the current study evaluates the sustainability performance of 50 rainfed farms in the Zaër Region of northwestern Morocco using the innovative Indicateurs de Durabilité des Exploitations Agricoles/IDEA method (indicators of farming systems sustainability), which encompasses agro-ecological, social and economic criteria to assess the three pillars of sustainability. Customized assessment criteria and a tailored scoring system, specific to the region’s context, are employed, resulting in a comprehensive grid with 18 indicators across nine components. Data analysis and visualization were facilitated using statistical methods and an Excel macro. The findings reveal limitations in the sustainability of the surveyed farms. Socio-territorial factors, including issues with product quality, insufficient farmer training, limited workforce mobilization and low social involvement, contribute to the overall sustainability challenges. Agroecologically, low crop diversification, inadequate space management, and excessive reliance on chemical inputs are identified as areas of concern. On the economic scale, low specialization levels hinder economic viability despite some financial autonomy. The study emphasizes the need for interventions to enhance sustainability in rainfed agrosystems. Recommendations are provided to address socio-territorial constraints, improve agricultural practices, and promote economic viability. The findings have implications for policymakers, farmers and stakeholders, offering valuable insights for prioritizing strategies and actions to achieve sustainable agriculture in arid and semi-arid regions.